Situational Leadership in Developing Qur’an Memorization Programs in Islamic Secondary Education - Dini Amanda Rochmah; Moh. Syamsul Falah (Journal of Educational Management Research, 2026)
This study aims to examine the implementation of situational leadership in the development of a Qur’an memorization (tahfidz) program, focusing on leadership practices, program management, and their contribution to program sustainability and quality improvement. The study employed a qualitative case study approach involving the principal, curriculum vice principal, program coordinator, tahfidz teachers, and students. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that situational leadership was implemented adaptively through four leadership styles: telling, selling, participating, and delegating. These approaches were applied across the planning, implementation, and evaluation stages of the tahfidz program according to teachers’ readiness and institutional needs. The study further demonstrates that situational leadership significantly contributed to strengthening teacher motivation, professionalism, collaboration, and program sustainability, which ultimately enhanced the overall quality of the educational institution. The findings imply that adaptive leadership practices are essential for supporting the continuous development of religious education programs in Islamic educational institutions.